Opacity, liquidity and disclosure requirements - André Stenzel; Wolf Wagner (Journal of Business Finance & Accounting, 2021)
We present a model that links the opacity of an asset to its liquidity. We show that while low-opacity assets are liquid, intermediate levels of opacity provide incentives for investors to acquire private information, causing adverse selection and illiquidity. High opacity, however, benefits liquidity by reducing the value of a unit of private information. The cross-section of bid–ask spreads of US firms is shown to be broadly consistent with this hump-shaped relationship between opacity and illiquidity. Our analysis suggests that uniform disclosure standards may be suboptimal; efficient disclosure can instead be achieved through a two-tier standard system or by subsidizing voluntary~disclosure.
Keywords: 650; asymmetric information; disclosure requirements; liquidity; opacity